ОБУЧЕНИЕ МЛАДШИХ ШКОЛЬНИКОВ РАБОТЕ С АРИФМЕТИЧЕСКИМИ ЛАБИРИНТАМИ НА УРОКАХ МАТЕМАТИКИ - Сапарова, А.А.; Утеулиев, Ш.Б. (SCIENCE and SOCIETY, 2024)
The article talks about the existence of arithmetic labyrinths and their widespread use in primary mathematics courses, as well as the distribution of arithmetic labyrinths in different educational and methodological complexes by academic year, their levels of complexity.
Keywords: tasks-jokes; tasks-fairy tales; riddles; mathematical tricks; puzzles; mazes; games